2015
DOI: 10.1016/j.jorganchem.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A study on the optical resolution of 1-isopropyl-3-methyl-3-phospholene 1-oxide and its use in the synthesis of borane and platinum complexes

Abstract: A 1-isopropyl-3-phospholene 1-oxide was prepared and the two enantiomers were isolated from the racemate by resolution using optically active TADDOL derivatives or the acidic Ca 2+ salts of (-)-O,O-diaroyl-(2R,3R)-tartaric acids. The single crystal X-ray structure of the 2 1-isopropyl-3-phospholene oxide -spiro-TADDOL 1:2 associate revealed the mode of binding between the host and guest molecules. The role of the interactions between the three molecules was supported not only by the contact data, but also forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…Moreover, a ( 1 ) 2 · (spiro‐TADDOL) diastereomer was prepared from the mixture of ethyl acetate and hexane. Based on our previous studies, the solvents with H‐donor and acceptor properties may be incorporated into the crystalline structure . The solvents may change the mode of binding, as well as the secondary interactions, and consequently the composition of the diastereomer.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, a ( 1 ) 2 · (spiro‐TADDOL) diastereomer was prepared from the mixture of ethyl acetate and hexane. Based on our previous studies, the solvents with H‐donor and acceptor properties may be incorporated into the crystalline structure . The solvents may change the mode of binding, as well as the secondary interactions, and consequently the composition of the diastereomer.…”
Section: Resultsmentioning
confidence: 84%
“…Over the last few years, our research group elaborated efficient resolution methods for the preparation of 1‐substituted‐3‐methyl‐3‐phospholene 1‐oxides via the formation of diastereomeric complexes with TADDOL derivatives or with the calcium salts of tartaric acid derivatives . Moreover, the related optically active 3‐phospholenes were applied as ligands in the platinum‐catalyzed enantioselective hydroformylation of styrene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods involved in situ racemization of the phosphine oxide or its derivative under the resolution conditions. [55][56][57][58][59][60][61][62][63][64][65] The aim of this study is to demonstrate that our resolution methods can be applied to a wider substrate scope. [40][41][42][43][44] However, many enantioseparation methods developed for chiral phosphine oxides comprise classical resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…44,54 Our research group found that TADDOL derivatives and the Ca 2+ salts of tartaric acid derivatives were suitable resolving agents to separate the enantiomers of several 5-and 6-membered P-heterocyclic phosphine oxides having various substitution patterns. [55][56][57][58][59][60][61][62][63][64][65] The aim of this study is to demonstrate that our resolution methods can be applied to a wider substrate scope. Herein, we report the resolution of ethyl-(2methylphenyl)-phenylphosphine oxide and the purification strategies for the corresponding enantiomeric mixtures, as a detailed example for the preparation of optically active acyclic diaryl-alkylphosphine oxides.…”
mentioning
confidence: 99%